Stormwater Runoff and Tidal Flooding Transform Dissolved Organic Matter Composition and Increase Bioavailability in Urban Coastal Ecosystems. Issue 7 (15th July 2021) - Smith, Matthew A.; Kominoski, John S.; Gaiser, Evelyn E.; Price, René M.; Troxler, Tiffany G.
Abstract: Coastal drainages contain multiple sources of dissolved organic matter (DOM) that influence OM transformation and fate along inland‐to‐marine gradients. Anthropogenic activities have altered DOM composition in urban drainages, thereby influencing in‐stream breakdown rates, primary productivity, and downstream export. Yet, it is uncertain how hydrologic conditions (i.e., rainfall, tides, shallow groundwater) interact with different sources of DOM to regulate the transformation and export of DOM through urban coastal drainages. We characterized how seasonal changes in hydrologic conditions influence DOM composition and bioavailability in tidally influenced drainages in Miami, FL, USA. We estimated the quality and bioavailability of DOM using compositional proxies based on fluorescence spectroscopy, including parallel‐factor analysis, and measured dissolved organic carbon degradation during laboratory incubations containing a local bacterial community. Interactions between stormwater runoff and tidal amplitude increased the bioavailability of DOM and were positively correlated with predominantly humic‐like components in the wet season and protein‐like components in the dry season. Further, increases in tryptophan fluorescence intensity corresponded with elevated concentrations of Escherichia coli and enterococci—likely from waste‐impacted groundwater—and contributed substantially to overall DOM bioavailability. Our results provide new evidence of an urban priming effect in which labile autochthonous DOM from anthropogenic sources facilitates microbial degradation of DOM that is driven by seasonal differences in stormwater runoff and tides. As hydrologic conditions in near‐shore aquatic ecosystems shift with urbanization and climate‐driven changes in sea‐level rise, increases in autochthonous sources of bioavailable DOM may impact ecosystem metabolism and affect the quality of DOM exported downstream. Plain Language Summary: In coastal watersheds, runoff and tides mobilize large amounts of dissolved organic matter (DOM) from rivers to the ocean. Human activities in cities can change the composition of this matter and influence rates of carbon removal and downstream export. In coastal cities, the effect of storm runoff and tides on this transformation is still uncertain. To explore this, we collected water from canals in urban subtropical watersheds (Miami, USA) during seasonal tidal events and analyzed the chemical composition of organic matter dissolved in the water. We found that increases in urban‐derived organic material, likely from waste in groundwater sources, are easily broken down by microbes and can lead to the breakdown of other, less easily degraded organic matter. This process is often greatest during high tide in the subtropical wet season. Our research enhances understanding of how variation in and relationships among urban DOM from various sources increase biological activity and rapid processing of organic matter in urban coastal waters. The processing of organic matter in urban waters is a critical function that influences nutrient removal and multiple aspects of water quality. Key Points: Seasonal runoff and tides control dissolved organic matter (DOM) composition and bioavailability in coastal urban drainages DOM bioavailability is related to the proportion of protein‐like components in coastal urban drainages Proteinaceous DOM likely from waste‐impacted groundwater and autochthonous production may prime microbial degradation of humic DOM